2013
DOI: 10.4028/www.scientific.net/msf.773-774.496
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion Printed Graphene/Polycaprolactone/Composites for Tissue Engineering

Abstract: In this work fibres and complex three-dimensional scaffolds of a covalently linked graphene-polycaprolactone composite were successfully extruded and printed using a melt extrusion printing system. Fibres with varying diameters and morphologies, as well as complex scaffolds were fabricated using an additive fabrication approach and were characterized. It was found that the addition of graphene improves the mechanical properties of the fibres by over 50% and in vitro cytotoxicity tests showed good biocompatibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 18 publications
(23 reference statements)
0
18
1
Order By: Relevance
“…The covalently linked composites exhibit far better homogeneity and as a result, both Young's modulus and tensile strength more than double with significant improvement in conductivity. 92 In vitro cytotoxicity testing of the materials showed good biocompatibility resulting in promising materials for use as conducting substrates for the electrically stimulated growth of cells.…”
Section: Solution Mixingmentioning
confidence: 99%
See 2 more Smart Citations
“…The covalently linked composites exhibit far better homogeneity and as a result, both Young's modulus and tensile strength more than double with significant improvement in conductivity. 92 In vitro cytotoxicity testing of the materials showed good biocompatibility resulting in promising materials for use as conducting substrates for the electrically stimulated growth of cells.…”
Section: Solution Mixingmentioning
confidence: 99%
“…In the case of graphene dispersions, the rheology of the ink needs to be controlled by concentration, 4 whereas, for the composite, the polymer aids the processing. 92 CCG has been used in printed patterns for the fabrication of flexible electronics, 106 and in a composite with polycaprolactone as a melt extruded scaffold for tissue engineering. 92 In this latter paper, graphene/PCl composite fibers (Figures 8a and b) were extrusion printed onto a glass substrate to form circular 3D scaffolds (Figure 8c).…”
Section: Inkjet Printingmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been shown that the materials developed using this CCG are biocompatible and appropriate for cell culture. 20,21,23,27 …”
Section: Preparation Of Chemically Converted Graphene Oxide Dispersionmentioning
confidence: 99%
“…[12][13][14][15][16] Graphene, a planar monolayer of carbon material arranged in a honeycomb lattice with excellent mechanical, electrical and thermal properties, has been shown to be an excellent material with which to modify biopolymers for tissue engineering without affecting their biocompatibility or processability. [17][18][19][20][21][22][23] The advantage of graphene over the other carbonaceous fillers, e.g. carbon nanotubes, is its facile and inexpensive synthesis and its potential for scaled-up manufacturing in solution form.…”
Section: Introductionmentioning
confidence: 99%